Pulmonary Hernia in a Two-Year-Old Child - Jenna Fine; Bryan S. Walters; Alysia A. Agnoni; Christopher P. Coppola; Ronald J. Scorpio; Alfred P. Kennedy (Case Reports in Surgery)
Pulmonary hernia, also known as lung herniation or intercostal herniation, is best explained as the lung parenchyma protruding beyond the confines of the thoracic wall. This rare finding can be classified as congenital or acquired. Acquired pulmonary herniations are often the complication of blunt or penetrating trauma to the chest wall. This report describes a two-year-old male who fell onto a rigid post, striking his left lower chest. Imaging studies demonstrated a small pneumothorax as well as pulmonary herniation. The patient underwent a diagnostic thoracoscopy and repair of a pulmonary hernia within the 7th intercostal space without complication. In this case report, we aim to add to the limited body of existing literature on the surgical management of pulmonary hernias.